Di-μ-aqua-bis(μ-pyridazine-4-carboxylato-κ(2) N:N′)bis[triaqua(pyridazine-4-carboxylato-κ(2) O,O′)lead(II)] dihydrate - Starosta, Wojciech (International Union of Crystallography, 2009)
The structure of the title compound, [Pb(2)(C(5)H(3)N(2)O(2))(4)(H(2)O)(6)]·2H(2)O, is composed of dimeric molecules in which two symmetry-related Pb(2+) ions are bridged by a pair of two pyridazine-4-carboxylate ligand molecules via both heterocyclic N atoms and two water O atoms. Each Pb(2+) ion is also coordinated by two carboxylate O atoms and three water O atoms, leading to a highly irregular coordination polyhedron around Pb(2+). The dimers are interconnected by hydrogen bonds between coordinated and uncoordinated water molecules and the carboxylate O atoms. O—H⋯N interactions are also present.